ANALISIS KEPUASAN KONSUMEN DAN BAURAN PEMASARAN PADA AGROINDUSTRI KOPI BUBUK CAP JEMPOL DI KOTA BANDAR LAMPUNG - Putri, Vita Dwi; Affandi, Muhammad Irfan; Nikmatullah, Dewangga (Lampung University, 2020)
This study aims to analyze the level of consumer satisfaction of coffee powder and the marketing mix of coffee powder agroindustry in Bandar Lampung City. The research method used was a case study. Research location was determined purposively. The number of interviewed sample was 60 respondents that were chosen by snowball sampling. Respondents of this study consisted of consumers of coffee powder, owners, industry and trade in Bandar Lampung City, and expert of University Lampung chosen by snowball sampling. The study was conducted in February-April 2018. The data analysis method used has the analysis of the Customer Satisfaction Index (CSI) and analysis descriptive. The results showed that: consumers of Cap Jempol coffee powder in Bandar Lampung City were in satisfied criteria. The marketing mix for agroindustry has implemented marketing strategy (marketing mix).Keywords :agroindustry, consumer satisfaction, coffee powder, marketing mix